Personalized Medicine and Pharmacogenomics: A Comprehensive Review - Alkhatib, Ahed J (International Journal of New Medicine, 2025)
Pharmacogenomics enables the development of tailored therapy for individual patients. Momentous advances in DNA sequencing and genotyping have accelerated the discovery of single-nucleotide polymorphisms and mutations that influence drug metabolism, transport, and targets. Multi-analyte arrays have been developed to simultaneously assess genetic variants, aiding in the treatment of oncology and cardiology conditions. These advances are driving the implementation of pharmacogenomics in actual clinical settings and ushering in a paradigm shift toward individualized medicine.